Решить уравнение : а) х^4-65х^2+64=0. б)(х^2-3х)^2-2х^2+6х-8=0
Решить уравнение :
а) х^4-65х^2+64=0.
б)(х^2-3х)^2-2х^2+6х-8=0
Ответ(ы) на вопрос:
а) Замена: t=x^2, значит t>=0
t^2-65t+64=0
D=4225-256=3969=63^2
t1=(65-63)/2=1
t2=(65+63)/2=64
Обратная замена:
x^2=1
x1=-1; x2=1
x^2=64
x1=-8; x2=8.
б) (х^2-3х)^2-2(х^2-3x)-8=0
Замена: t=x^2-3x
t^2-2t-8=0
D=4+32=36=6^2
t1=(2+6)/2=4
t2=(2-6)/2=-2
Обратная замена:
1) x^2-3x=4 <=> x^2-3x-4=0
D=9+16=25=5^2
x1=(3-5)/2=-1
x2=(3+5)/2=4
2) x^2-3x=-2 <=> x^2-3x+2=0
D=9-8=1
x1=(3-1)/2=1
x2=(3+1)/2=2
[latex]x^4-65x^2+64=0\\\begin{cases}x^2_1+x^2_2=65\\x^2_1*x^2_2=64\end{cases}\\x^2_1=64\ ;x_2=1\\x_1=^+_-8\ ;x_2=^+_-1[/latex]
[latex](x^2-3x)^2-2x^2+6x-8=0\\(x^2-3x)^2-2(x^2-3x)-8=0;x^2-3x=a\\a^2-2a-8=0\\\begin{cases}a_1+a_2=2\\a_1*a_2=-8\end{cases}\\a_1=4\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ a_2=-2\\x^2-3x-4=0\ \ \ \ \ x^2-3x+2=0\\x_{1,2}=\frac{3^+_-5}{2}\ \ \ \ \ \ \ \ \ \ \ \ x_{3,4}=\frac{3^+_-\sqrt5}{2}\\x_1=4\ ;x_2=-1\ \ \ \ x_3=\frac{3+\sqrt5}{2}\ x_4=\frac{3-\sqrt5}{2}[/latex]
Не нашли ответ?
Похожие вопросы